LINGUISTIC CREATIVITY AND ITS IMPLICATIONS ON ELT - Ginting, Daniel (Jurnal Bahasa Lingua Scientia, 2012)
There are at least two reasons why linguistic creativity is appealing and hence worth discussing in this paper: Firstly, linguistic creativity serves profound explanation to individual differences in the sense that people have unique ways to express themselves in a language. In the perspective of a stilistic approach we can sense how literary authors are obviously unique to one another in terms of their writing styles even when they have to depict the same theme. Secondly, linguistic creativity also serves profound explanation to the fact that a human?s language is basically a product of his mental  ability that operates according to the rules of grammar. In this sense, human?s linguistic creativity is viewed as rule-governed creativity.